170k views
0 votes
-2(3x-4) - x-3 = 33

User Stsquad
by
6.0k points

2 Answers

2 votes

Answer:

x = -4

Explanation:

-2(3x -4) -x -3 = 33 Distribute the -2

(-2)(3x) -2(-4) -x -3 = 33

-6x +8 -x -3 = 33 Combine like terms

-7x + 5 = 33 Subtract 5 from both sides

-7x = 28 Divide both sides by -7

x = -4

User Bhanu Sinha
by
6.0k points
5 votes

Answer:

x = -4

Explanation:

First distribute the -2 to the parentheses (3x-4)

That gives you -6x+4

So, -6x+8-x-3=33

Combine like terms for the x.

-6x-x= -7x

Combine like terms for the integers.

8-3=5

So, -7x+5=33

Subtract 5 on both sides of the equation

-7x=28

Divide by -7 on both sides

x = -4

User CpnCrunch
by
6.5k points